A Comparative Evaluation of Nutritional Composition of Deep Sea and Coastal Shrimp off South-west Coast of India - Jose Fernandez, T.; Anandan, R.; Zynudheen, A. A. (Fishery Technology, 2018)
The chemical composition of deep-sea shrimp Aristeusalcocki, Heterocarpus gibbosus, Plesionika spinipus andMetapenaeopsis andamanensis harvested by deep-seashrimp trawlers operating off the south west coastof India were evaluated and the nutritional compositionwas compared with coastal shrimpFenneropenaeus indicus and Penaeus monodon. Amongdeep sea shrimp, the highest protein content of22.82% was observed in H. gibbosus, whereas proteincontent in other species were in the range of 18.81– 22.33%. Protein content in P. monodon and F. indicuswere estimated as 17.46 and 19.23% respectively.Higher protein content in the muscle of deep seashrimp indicates that deep sea shrimp meat can bea good source of amino acids. Among the speciesstudied, fat content was comparatively high inA. alcocki (3.18%) followed by H. gibbosus (2.72%).Deep sea shrimp were found to have higher mineralcontent and have a higher amount of calcium andsodium when compared to coastal shrimp. Theessential and non-essential amino acids were foundhigher in A. alcocki (17.78 and 15.71 g 100 grespectively) than other deep sea and coastal shrimp.